Proximity: Kedekatan yang Diusung Citizen Jounalism - Ida Nuraini Dewi Kodrat Ningsih (Universitas Multimedia Nusantara, 2015)
New technology and media, brings kind of new information in the name of “new journalism” now. This what we called “citizen journalism.” The medium which placed common people to be one of producer or even the distributor as the information. On this paper the writer resume a research about “Proximity which brought by Citizen Journalism.” This reserach, was tried to know how the perception of Indonesian student and alumny who studied abroad about citizen journalism and its proximity. The respondens was collected by purposive sampling and snowballing and from this research, we would know that by the present of citizen journalism, nowadays people are easier to get much more and various information from anywhere. Some respondens said that it kind of helpfull, which these information not only inform them about something but also brings what it calls “proximity” inside its content. They feel it because when the respondens read or heard information about something from their hometown or elsewhere, citizen journalist-who has tendency as a eyewitness or part of the insider/local people- could brought them “intimacy” or “proximity”which can help them to feel close with the happening informed. Kata Kunci: inimacy, jurnalisme warga, kedekatan, persepsi, proximity